Long-distance commuting and dispersed socio-economic benefits of connectivity. Issue 3 (2nd September 2017) - McKenzie, Fiona Haslam; Hoath, Aileen
ABSTRACT: Long-distance commuting (LDC) in Australia has become an entrenched workforce practice. Work force mobility is not limited to the mining sector although for more than a decade, the scale of LDC in the resources industries has been contentious. A diverse range of workforce supply, logistical and employee preference reasons have contributed to the existence of LDC arrangements throughout Australia across many industry sectors. The economic and social consequences of LDC are also varied and complex. This article reports on research conducted with three case-study communities in rural, regional and remote locations where local residents regularly work long periods of time away from home (source communities) in the mining industry. The research analysed the socio-economic impacts on the workers, families, communities and businesses from source communities. Results show that LDC had benefits and by synthesising the key learnings of LDC, potential benefits for regional and community development are highlighted.